2018
DOI: 10.1615/intjmedmushrooms.2018028370
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidative and Hypo-cholesterolemic Effects of Lingzhi or Reishi Medicinal Mushroom, Ganoderma lucidum (Agaricomycetes), in Ameliorating Cardiovascular Disease

Abstract: Oxidative stress (OS) and hypercholesterolemia have been linked with a heightened risk of cardiovascular disease (CVD). Because of the numerous drawbacks of synthetic antioxidants and cholesterol-lowering drugs, natural antioxidative and hypocholesterolemic agents are of immense importance. This study was designed to determine both the OS-attenuating and cholesterol-lowering capacities of the hot water extract (HWE) and of five solvent-solventpartitioned fractions of Ganoderma lucidum. In vitro antioxidative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…Previous studies have showed that a reduction in concentrations of LDL cholesterol could markedly reduce the risk of stroke and coronary heart disease incidence and mortality [35]. Many previous studies have also shown that mushroom has excellent effects on lowering the LDL content [36,37]. Therefore, dietary FVS could benefit the health of piglets through lowering the LDL content in serum.…”
Section: Fecal Short Chain Fatty Acids Production and Serumal Indicesmentioning
confidence: 99%
“…Previous studies have showed that a reduction in concentrations of LDL cholesterol could markedly reduce the risk of stroke and coronary heart disease incidence and mortality [35]. Many previous studies have also shown that mushroom has excellent effects on lowering the LDL content [36,37]. Therefore, dietary FVS could benefit the health of piglets through lowering the LDL content in serum.…”
Section: Fecal Short Chain Fatty Acids Production and Serumal Indicesmentioning
confidence: 99%
“…Many edible mushroom species analysed for their medicinal properties have been found to contain many active ingredients. These compounds have been shown to strengthen the immune system, have anti-carcinogenic and cholesterol-lowering properties and act as protective agents against hepatitis (De Silva et al, 2012;Rahman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The State Pharmacopoeia of the People's Republic of China (2000) has incorporated G. lucidum as the potent replenisher of Qi (life force), salient mind soothening and cough relieving as well as anti-asthmatic agent [2]. Modern medicinal sector also acknowledge its inclusion as a therapeutic agent against numerous physiological disorders including, but not limited to, antioxidant, anti-in ammatory, antitumor, anticancer, antimicrobial, immunomodulatory and hepatoprotective agent [3][4][5][6][7]. Content of more than 400 gano-components had accredited Ganoderma as the "fungal biofactory", "panacea" and the "elixir of life" [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Modern medicinal sector also acknowledge its inclusion as a therapeutic agent against numerous physiological disorders including, but not limited to, antioxidant, anti-in ammatory, antitumor, anticancer, antimicrobial, immunomodulatory and hepatoprotective agent [3][4][5][6][7]. Content of more than 400 gano-components had accredited Ganoderma as the "fungal biofactory", "panacea" and the "elixir of life" [3][4][5][6][7]. Gano-components conferring medicinal values range from polysaccharides to triterpenes, sterols, proteins, peptides, fatty acids and vitamins [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation